The relationship between inventive thinking and intelligence among talented middle school students in Makkah Al-Mukarramah - Al-Osimi, Sara Awed (Journal of Educational and Psychological Sciences, 2023)
The research aimed to reveal the level of inventive thinking and the level of intelligence among gifted female students at Middle Schools in Makkah Al-Mukarramah in the Academic Year (1443 AH), and to explore the relationship between inventive thinking and intelligence. To achieve the objectives of the research, the researcher used descriptive correlative approach, and the measure of inventive thinking and the successive Raven matrices “YAS” was used to collect data, the community consisted of (633) talented female students at the Middle Schools in the City of Makkah Al-Mukarramah, the number of respondents was (376). The results indicate high level of inventive thinking among the study sample, and the dimension of curiosity came in the first place, followed by higher thinking and sound logic, and finally the dimension of risk tolerance. The results of the study also showed a high level of intelligence for most of the sample members, where the average value of performance was (24.77) and the standard deviation (7.64), while there is a positive and statistically significant correlation between intelligence and the tendency to take risks.
Keywords: inventive thinking; IQ test; talents; advanced raven matrices; invention; thinking skills